Determination of critic period of irrigation on wheat crop - Souza, Fernando Goulart de Andrade e; Tubelis, Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The scope of this work was to determine the critical periods of wheat crop with respect to water requirement. It is based on an experiment having duration of irrigation period as treatment. The wheat crop showed to have two antagonistic critical periods with respect to water supply. The first one, from affiliation up to first half of flowering stage, when the water supply is benefic to yield; and the other one, from the second half of flowering until before the milk stage, when the water supply is harmful to yield. Wheat crop yield equations as a function of applied water in periods of ten days, were calculated. The equation that showed the highest correlation coefficient was: W = 362.4 + 13.866 P(50-69) r = 0.9049 where W is the wheat yield in kg/ha and P(50-59) the applied water in the period (50-59) days, in milimeters. The variation of wheat yield per encrease of 1 milimeter in the applied water was analysed. The greatest value of variation was + 17.028 kg/ha.mm to the (30-39) days period.